Types of syncretism in the clitic systems of Romance - Pescarini, Diego (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2007)
In this paper I will discuss the hypothesis according to which every clitic system bears an elsewhere item, i.e., a non-specific clitic that can be inserted when the insertion of more specific items is blocked by independent constraints. In my opinion the insertion of an elsewhere clitic accounts for different phenomena such as synthetic clusters (Bonet 1991, Harris 1994, Pescarini to appear) and absolute syncretisms (Calabrese 1994, Loporcaro 1995). I will support this claim on the basis of the data displayed by some Italian dialects.